Lithium Suppresses Hedgehog Signaling via Promoting ITCH E3 Ligase Activity and Gli1–SUFU Interaction in PDA Cells - Wang, Xinshuo; Fang, Zijian; Wang, Anlin; Luo, Cheng; Cheng, Xiaodong; Lu, Meiling (Frontiers in Pharmacology, 2017)
Dysregulation of Hedgehog (Hh) signaling pathway is one of the hallmarks of pancreatic ductal adenocarcinoma (PDA). Lithium, a clinical mood stabilizer for the treatment of mental disorders, is known to suppress tumorigenic potential of PDA cells by targeting the Hh/Gli signaling pathway. In this study, we investigated the molecular mechanism of lithium induced down-regulation of Hh/Gli1. Our data show that lithium promotes the poly-ubiquitination and proteasome-mediated degradation of Gli1 through activating E3 ligase ITCH. Additionally, lithium enhances interaction between Gli1 and SUFU via suppressing GSK3β, which phosphorylates SUFU and destabilizes the SUFU-Gli1 inhibitory complex. Our studies illustrate a novel mechanism by which lithium suppresses Hh signaling via simultaneously promoting ITCH-dependent Gli1 ubiquitination/degradation and SUFU-mediated Gli1 inhibition.